2014
DOI: 10.9734/ejmp/2014/7702
|View full text |Cite
|
Sign up to set email alerts
|

The Antidepressant-like Effect of Hyperbrasilol B, A Natural Dimeric Phloroglucinol Derivative is Prevented by Veratrine, a Sensitive-Voltage Na+ Channel Opener

Abstract: This work was carried out in collaboration between all authors. Author FBC contributed with the design of the study; performed the In vivo experiments, statistical analysis an literature searches; wrote the protocol and the first draft of the manuscript. Author SS performed all chemical procedures. Author LGM contributed with In vivo experiments and statistical analysis. Author PMC performed In vitro experiments. Author GVP planned and supervised all chemical experiments. Author CWN planned and supervised all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The results showed that the antidepressant-like effect might be due to the alterations in the sodium ion gradient. 41…”
Section: Naturally Occurring Methylene-bridged Dimersmentioning
confidence: 99%
“…The results showed that the antidepressant-like effect might be due to the alterations in the sodium ion gradient. 41…”
Section: Naturally Occurring Methylene-bridged Dimersmentioning
confidence: 99%
“…Other pharmacological effects of phloroglucinols include antioxidant, antidepressant, antiviral (including effectiveness against SARS-CoV-19), antinociceptive etc. [ 23 , 27 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%